2017
DOI: 10.1097/sla.0000000000001808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Re-resection to Achieve R0 Status on Survival in Patients With Pancreatic Cancer

Abstract: FS analysis with intraoperative re-resection should be performed routinely in patients undergoing pancreatic cancer surgery with the aim to achieve a R0 resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 41 publications
5
42
0
3
Order By: Relevance
“…The poorer prognosis of the pancreatobiliary subtype could probably be explained by a disseminating growth behavior, perineural sheet invasion, and by a distinct desmoplastic stromal reaction 22 . The median overall survival for the pancreaticobiliary subtype was 52 months (95% CI: 37–68 months), which is comparable to resected patients with ductal adenocarcinoma, with an overall survival up to 36 months in selected patients in our center 23 . Localization of the tumor itself could be one of the main reasons for better survival rates, due to the occurrence of early symptoms like obstructive jaundice and pain by occluding the distal bile duct.…”
Section: Discussionsupporting
confidence: 49%
“…The poorer prognosis of the pancreatobiliary subtype could probably be explained by a disseminating growth behavior, perineural sheet invasion, and by a distinct desmoplastic stromal reaction 22 . The median overall survival for the pancreaticobiliary subtype was 52 months (95% CI: 37–68 months), which is comparable to resected patients with ductal adenocarcinoma, with an overall survival up to 36 months in selected patients in our center 23 . Localization of the tumor itself could be one of the main reasons for better survival rates, due to the occurrence of early symptoms like obstructive jaundice and pain by occluding the distal bile duct.…”
Section: Discussionsupporting
confidence: 49%
“…With accurate assessment of resection margins by a standardized pathological examination protocol using LEEPP and DWMSIs, and with a single de nition of R1 using the 1 mm de nition, our study showed marked differences in the R1 resection rates for PD and DP when compared with the published rates of R1 resection [22][23][24][25][26]. In the current study, the rates of R1 resection were similar to the recently reported data for patients who underwent upfront surgery [27].…”
Section: Discussionsupporting
confidence: 82%
“…Studies have described contradictory findings, with some suggesting the useful impact of achieving negative pancreatic neck margin at the time of surgery, 19 whereas others indicate no significant improvement in overall survival. 17,[20][21][22][23][24][25][26][27][28][29] Positive margin status on FS has been shown to be a negative independent predictor of overall survival, 19 but not when other factors are taken into consideration, such as large tumor size, 17,22 lymphovascular invasion, 17 and perineural invasion, 22,24 among others.…”
Section: Discussionmentioning
confidence: 99%